Analysis of the effect of physical-mechanical performance of two-level knitted fabrics on shape stability - Shogofurov Shaxboz Shokirjon ugli; Rahmatova Sadokat Umarjonovna; Uralov Lazizbek Saidnazar ugli; Kholikov Kurbonali Madaminovich (International Journal on Orange Technologies, 2021)
The article presents the results of the analysis of physical and mechanical properties of 4 variants of knitted fabric